Dynamic Hedge Mapping IHSG: Bukti Rolling regression 60-Hari pada Bitcoin, Emas, Obligasi, dan USD - Jeffry Halim; Vicky Oktavia; Agus Prayitno; Amalia Nur Chasanah (Jurnal Ilmiah Global Education, 2026)
This study examines whether four alternative assets Bitcoin, gold, government bonds, and the United States dollar provide protection against declines in the Indonesia Stock Exchange Composite Index (IHSG). The objective is to determine which assets act as hedges for returns and which serve as volatility safe havens during turbulent market conditions. Using daily log returns from February 2022 to April 2025, the study applies simple linear return regressions, volatility regressions constructed from 10-day rolling standard deviations, and 60-day rolling return regressions to capture time-varying relationships. The results show that the US dollar consistently exhibits a negative and statistically significant relationship with IHSG returns, indicating a reliable hedging function. In contrast, government bonds, gold, and Bitcoin display positive return betas, implying pro-cyclical behavior rather than defensive characteristics. In volatility analysis, the US dollar and government bonds record the smallest sensitivity to index volatility, while Bitcoin and gold amplify market risk. Time-varying (rolling) estimates reinforce these patterns: the dollar’s defensive role persists across normal and crisis episodes, whereas the other assets rarely show sustained negative betas. In conclusion, for the observed period and market context, the United States dollar is the most effective hedge against IHSG declines; government bonds contribute to volatility stabilization; gold offers limited diversification benefits; and Bitcoin does not function as a dependable defensive asset in the Indonesian equity market.